Towards human cardiac new approach methodologies (NAMs) to evaluate the combination of repolarization prolonging and shortening drugs: a pilot study - Geiger, Robert M.; Serna, Carlos; Bhardwaj, Bhavya; Feaster, Tromondae K.; Blinova, Ksenia (Frontiers in Drug Discovery, 2025)
Background and PurposeNonclinical human cardiac new approach methodologies (NAMs), including human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) combined with multielectrode array (MEA) represent a highly predictive in vitro model for identifying drug-induced cardiac liabilities of individual drugs. Here, we extend the use of an in vitro cardiac NAM to evaluate the safety of a drug combination including moxifloxacin, an antibiotic, and QT prolonging drug, and cobicistat a pharmacokinetic booster shown to shorten repolarization in vitro.MethodsTo generate the in vitro cardiac NAM, MEA coupled with hiPSC-CMs were cultured for 7–8 days. Cells were treated with moxifloxacin and cobicistat individually or in combination and changes in electrophysiology and contractility were evaluated.ResultsThe combination of cobicistat and moxifloxacin resulted in a concentration-dependent shortening of the corrected field potential duration (FPDcF) relative to both vehicle control and moxifloxacin alone. This effect was observed at near clinical Cmax concentrations of cobicistat and moxifloxacin. Evaluation of local extracellular action potentials (LEAP) revealed early afterdepolarizations (EADs) with supratherapeutic concentrations of moxifloxacin which were subsequently eliminated by the addition of cobicistat at therapeutic concentrations. Finally, the Comprehensive in vitro Proarrhythmia Assay (CiPA) Torsades de Pointes (TdP) risk tool categorized moxifloxacin treated cells as having a high or intermediate risk probability for TdP while concomitant treatment with cobicistat resulted in a low-risk categorization.ConclusionWe conclude that cobicistat can attenuate moxifloxacin induced FPDcF prolongation at clinically relevant concentrations in vitro. Taken together, this work provides a foundation to evaluate drug combinations in vitro to aid regulatory decision-making and reduce the dependence on animal studies.